The study on flexible manufacturing system in building decoration stone processing. Issue 1 (1st April 2022) - Du, F; Zhao, M; Zhang, P
Abstract: Stone materials are widely used in interior and exterior decoration design and public facilities construction. They are one of the essential materials in the construction and decoration field. With the increase in demand of the personality and quality of the decoration materials, intelligent manufacturing of stone processing must be required. With the development of manufacturing technology, especially the rapid development of automatic control technology, CNC machining technology and industrial robot technology, flexible manufacturing technology (FMI) have been used. In the paper an intelligent flexible processing system of stone is designed, which is composed with CNC processing tool, material transmission and storage system, computer control system and stone processing process monitoring system. It can realize fully automatic and intelligent flexible production from building stone processing, stone handling, comprehensive waste treatment, tool optimization and computer control. The calculation method of optimal equipment layout is explained and the field layout of each unit of FMS is given. The purpose of this project is to improve the intelligent level of building decoration stone processing through flexible manufacturing technology and increase production efficiency and material utilization as well as to satisfy needs of diversified product.